Lung ultrasound for diagnosis of pneumothorax in an infant - Tiago Henrique de Souza; Marina Pavan Giatti; Marcelo Barciela Brandão (Wolters Kluwer Medknow Publications, 2016)
Point-of-care ultrasound provides rapid and accurate diagnostic imaging in an acute care setting. While thoracic ultrasonography has proved to be a useful technique for adults in the emergency department and intensive care units, few studies have evaluated this technique in children. In this case, we describe the presence of a pneumothorax, identified by point-of-care ultrasound in a 4-month-old infant in postoperative care after cardiac surgery. The infant presented with mild respiratory distress. A resident physician performed the exam, after recently completing ultrasound training.